The French Colonial Strategy in the Algerian Desert - Chatra, Khireddine Youssef (Al-Adab Journal, 2021)
The French colonial expansion in the Algerian desert is considered a pivotal point in the modern history of that area. This is mainly because the ultimate goal of the French was to separate north Algeria from the southern provinces. This explains placing the south under a special military administration, which served other colonial purposes such as facilitating the expansion into West Africa, and linking the various French colonies in the region even though the geopolitical context of the area did not support such tactics.This paper reviews the European, and particularly the French, exploratory, political, economic and missionary ventures in the Algerian deserts both before and after the French colonization. It also discusses the colonial and strategic motives for the French attempts to dominate this particular area as well as the stages, characteristics, and impact of this expansionist venture.The researchers propose that at present, France still adopts the same practice of using the anthropological, natural, and economic environment of any given state in order to achieve its political and economic goals.The paper concludes that the French administration was certain that its existence in Algeria, and its ability to hold on to its colonies in West and Sub-Saharan Africa, was determined by its dominance of the Algerian desert. In addition, this paper proposes that contemporary French foreign policy towards these African states has remained significantly unchanged.